2012
DOI: 10.1080/02763877.2011.596367
|View full text |Cite
|
Sign up to set email alerts
|

Reference, Readers' Advisory, and Relevance

Abstract: There is general agreement that the nature of reference services in academic and public libraries is undergoing dramatic change as a result of technological advancements and changes in user behaviors. Readers' advisory services offer libraries an opportunity to continue to remain relevant to their users. This article explores the similarities between the reference and the readers' advisory encounters and offers suggestions on more closely integrating these two essential services in both library practice and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…At times these groups have progressed on parallel courses that do not intersect, resulting in loss of opportunities for useful and fruitful collaboration." 22 In fact, these groups appear to be progressing on courses that are heading in opposite directions, which has negative implications for the future of RA education.…”
Section: Recent Trends In Ra Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…At times these groups have progressed on parallel courses that do not intersect, resulting in loss of opportunities for useful and fruitful collaboration." 22 In fact, these groups appear to be progressing on courses that are heading in opposite directions, which has negative implications for the future of RA education.…”
Section: Recent Trends In Ra Educationmentioning
confidence: 99%
“…30 Trott also writes about the importance of integrating RA into core services, as well as how education is central to this change, explaining, "Changing the false dichotomy that separates information-based questions from readingcentered questions in library public service can be addressed at all levels in the profession, from library school curricula to the day-to-day library practice." 31 One challenge to this change is that at the moment, whether taught by professors or practitioners, there is no agreement about what the role of a readers' advisor is, what the professional status of those offering RA services should be, nor a standard curriculum or institution from which the many forms of RA education can draw. Smith writes that "First, the profession needs to identify and define the nature of the readers' advisory role.…”
Section: The Future Direction Of Ra Educationmentioning
confidence: 99%
“…Since research has shown that people equate libraries with books, 96 we can capitalize on this opportunity "by expanding the value they offer to readers, viewers, and listeners who use our libraries." 97 As Trott suggests, we can increase our base and attract new users by serving their reading interests. 98 Given the fact that college students use libraries less in an electronic age and believe these institutions lack relevance in their lives, we need to give them reasons to return.…”
Section: How Does the Academic Library Benefit From Promoting Reading?mentioning
confidence: 99%
“…What college librarians do need though is training; our library schools should be preparing us to answer readers' advisory questions by teaching the necessary tools and strategies. 122 Academic libraries need to subscribe to online tools such as NoveList or What Do I Read Next, bookmark sites such as Whichbook.net, and buy readers' advisory reference tools such as the Genreflecting series, the ALA Readers' Advisory series, and Nancy Pearl' s Now Read This set of books. These tools can assist librarians; we, in turn, can teach our patrons (especially those who prefer to self-serve) how to use them.…”
Section: Readers' Advisory Services and Strategiesmentioning
confidence: 99%
See 1 more Smart Citation